If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 3a + -2a + -2b = 0 Combine like terms: a + 3a = 4a 4a + -2a + -2b = 0 Combine like terms: 4a + -2a = 2a 2a + -2b = 0 Solving 2a + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 2a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 2a + 0 = 0 + 2b 2a = 0 + 2b Remove the zero: 2a = 2b Divide each side by '2'. a = b Simplifying a = b
| 20logx=32.5 | | 12h-15=9h | | a+5a+b= | | 6a-5a+4b= | | 3x-y=20x+2y=23 | | 8m-12=5m | | 81x^8-82x^4+1=0 | | 2X+4.5Y=10 | | (D^3-3D^2+4)x=0 | | x^2+14x+14+y^2-2y=0 | | Y=-0.7x+340 | | 8x^3-12x^2-2x+3=0eq | | 10(s-8)=-125 | | (40-x)(16-x)=340 | | 12-1/3x=x | | 33-4x=9-9x | | 300-56x-x^2=0 | | x=12-1/3x | | 3x-4=11x-67 | | 0.56x+x=220 | | 0.2x+x=220 | | X+10+7x=-15-2x | | x^3=168 | | 7(4s)+1=231 | | 4(2l)+6=24 | | 1.8x=6.6 | | 14x^2-84x-126=0 | | (u-7)*8=24 | | 1/9x^6-81=0 | | 12=56-2*(3*x+4) | | 2u+14=4 | | f(e-a-c)=e(f-b-(1000-c)) |